P47 Systematic recall vs standard care, addressing the increased risk of re-infection in patients presenting with gonorrhoea. (23rd May 2012) - Fernando, K; Flew, S; Phattey, J; Harding, J; Fowler, T; Caley, M; Ross, J
Abstract : Background: Gonorrhoea is of increasing concern in UK, with the gonococcal resistance to antimicrobials surveillance programme reporting high levels of resistance to antibiotics. Prior history of gonorrhoea is a strong predictor of current infection, supporting the concept of a group of "core transmitters." The US Center for Disease Control advises retesting of patients with gonorrhoea 3 months after treatment to identify repeat infections. Current UK guidelines only recommend a test of cure at 2–4 weeks. Aim: To assess the feasibility, acceptability and effectiveness of routine retesting at a 3-month interval, in UK sexual health clinic attendees diagnosed with gonorrhoea. Methods: Attendees between November 2010 and June 2011 diagnosed with gonorrhoea were offered retesting 3–6 months after treatment, with a subsequent reminder to attend (recall arm). Re-attendance rates and frequency of gonorrhoea diagnosis were compared to a historic group who attended between October 2006 and April 2007, controlling for age, sex, sexual orientation and history of STI (control arm). Results: 242 patients were assessed in the recall arm. 95 (39%) re-attended within 6 months of initial attendance and 15 (6%) were positive for gonorrhoea. Of 202 controls, 44 (22%) re-attended within 6 months and 12 (6%) tested positive for gonorrhoea. Being actively recalled increased re-attendance at the clinic (β=2.2, p=0.001) but did not detect additional cases of gonorrhoea (β=1.2, p=0.9). Conclusion: These results strongly suggest that the CDC recommendation for re-testing for infection after 3 months is not an effective approach for unselected patients with gonorrhoea in the UK.